Synthesis and characterisation of thermomesogenic polysiloxanes with 2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione units in the main chain - Harabagiu, V.; Simionescu, Bc; Bilgin-Eran, B.; Cernenco, U.; Yagci, Y.; Hepuzer, Y.; Horn, M.; Pinteala, M. (Elsevier BV, 2002)
The synthesis of the first two liquid crystalline polysiloxanes bearing 3,6-diaryl-2,5-dihydropyrrolo-[3,4-c]pyrrole-1,4-dione units in their main chain are described. Investigations on their thermotropic phase behaviour by polarising microscopy reveal nematic or smectic enantiotropic phases, respectively.